Effect of Powtoon Based Animated Media on Biology Student Learning Outcomes at SMAN 2 Langsa - Yurida Yurida; Nursamsu Nursamsu; Dini Fitria (BIOPENDIX, 2026)
Powtoon based animated media is a learning medium that is very easy to use as teaching material for teachers. It can be created online and has many attractive animation features that can increase students' interest so that they do not get bored during the learning process. This study aims to determine the effect of Powtoon-based animation media on the learning outcomes of biology students at SMAN 2 Langsa. This study uses a quantitative research design with a quasi-experimental method and a pretest-posttest control group design using two sample classes, namely the experimental class and the control class. The research sample consisted of 28 students in the experimental class and 28 students in the control class. The results of the test instrument showed that the average pretest score for the experimental class was 44.64 (low) and for the control class was 43.75 (low), so the difference between the two classes was (0.89), while the average posttest score for the experimental class was 78.92 (moderate) and for the control class was 69.82 (moderate), resulting in a difference between the two classes of 9.1 (low). With a hypothesis test value of t count > t table or 4 > 1.673, it can be concluded that Ha is accepted and H₀ is rejected